PENGARUH METODE PERSALINAN, PENDIDIKAN, DAN PEKERJAAN TERHADAP PEMBERIAN AIR SUSU IBU (ASI) EKSKLUSIF DI RSIA KEMANG MEDICAL CAREJAKARTA SELATAN - Dimas Rafif Susetyo Suwarno (2020)
Breast milk is the best food that contains all the nutrients needed by babies aged 0-6 months. Indonesia still has problems in exclusive breastfeeding. The percentage stated by the Directorate General of Nutrition and Mother and Child Health of the Republic of Indonesia Ministry of Health 2014, that exclusive breastfeeding in Indonesia is still low (52.3%). This study aims to determine the effect of labor, education, and employment methods on exclusive breastfeeding. This sample was taken at rumah Sakit Ibu dan Anak Kemang Medical Care in South Jakarta. This type of research uses observational analytic with cross sectional approach. The sample consisted of 63 respondents. The research instrument used a questionnaire. Analysis of the data used Chi-square test. The result shows that there is a significant effect of the delivery method (p = 0,000), education (p = 0,000), employment (p = 0,000) and exclusive breastfeeding (p = 0,000). in nursing mothers as patients in the South Jakarta Kemang Medical Care Hospital for Children and Children in 2019.